Molecular Docking, Synthesis and Determination of Anticancer Potential of Novel Pyrimidine Derivatives: In vitro and in silico Characterization - Holam, Machhindra; Galatage, Sunil; Gaud, Supria; Kumbhar, Sanika; Devaru, Aishwarya; Inamdar, Saniya; Dokare, Sushma (Indian Journal of Pharmaceutical Education and Research, 2018)
Background: Lung and colon carcinoma are leading causes of mortality among all cancers and cases are increasing drastically. Chemotherapy plays vital role in the treatment of carcinoma and a new series of pyrimidine heterocycles attached to an azetidone has strong anti-cancer potential. Aim: Aim of current research work is to investigate the affinity of pyrimidine derivatives with the CDK4 protein using molecular docking. Materials and Methods: Antitumor activity of synthesized compounds was checked on HT29 and A549. The active site of the targeted protein identified by the help of docking techniques and the binding energies were calculated. Consequently, it was shown that compounds with docking scores of 6R, 6L and 6P have higher scores than those with scores in the series. Results: All the synthesized compounds were examined for GI50, TGI and LC50, while 6L and 6m showing predominant activity were tested for apoptosis. The compounds 6L and 6M exhibit the highest inhibitory activity on HT29 and A549 cell, the IC50 value of 10.0 and 17.2 µg/mL are respectively. The compounds 6M and 6L found significant anticancer potential on HT29 and A549 respectively. Both synthesized compounds successfully induce apoptosis potential in HT29 and A549 cell lines, which is confirmed by flow cytometry and DAPI staining. Conclusion: in the present study synthesized pyrimidine derivatives represent a viable strategy for the development of a novel anticancer moiety with potent anticancer and apoptotic effects. However; further in vivo animal studies are required to establish its efficacy in the treatment of cancer.
Keywords: Anticancer; Apoptosis; CDK4; Molecular docking; Pyrimidine